Psychological Safety and Collaborative Work Culture: The Path to Sustainable Organizational Performance - Nofiyanti, Nofiyanti; Fajrin, Andira; Sidiq, Ilham; jantrisia, Rio (International Journal of Social and Management Studies, 2025)
This study aims to analyze the role of psychological safety and collaborative work culture in improving sustainable organizational performance. Using a quantitative survey-based approach, data was collected from employees in various organizational sectors and analyzed using Structural Equation Modeling, Partial Least Square (SEM-PLS). The results indicate that psychological safety positively influences collaborative work culture and directly and indirectly impacts organizational performance through the mediation of collaborative culture. These findings reinforce previous literature emphasizing the importance of leadership and organizational culture in creating a work environment that supports openness, innovation, and long-term commitment. Collaborative work culture has proven to be a strategic pathway in promoting knowledge sharing, effective communication, and employee loyalty, which contribute to organizational sustainability. Additionally, visionary and transformational leadership plays a crucial role in creating psychological safety that encourages active employee participation. Practically, this research underscores that organizations need to integrate psychological safety and collaborative work culture into their human resource management strategies to enhance productivity, innovation, and sustainable competitiveness. Thus, these findings contribute to the development of organizational behavior theory and managerial implications for building adaptive and competitive organizations in the era of disruption